Comparison of Four Clinical Test for Assessing Hamstring Muscle Length - C. , Rajeswari; M.S. , Sundaram; P. , Senthil Selvam; A. , Viswanath Reddy; S. , Senthil; P. , Suganya (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To compare the four clinical tests for assessing hamstring muscle length. Need For the Study: Muscle tightness make the musculotendinous unit more susceptible to injury 1. It leads to posterior pelvic tilt, reduced lumbar lordosis, and causes low back pain. Hence, assessment of hamstring muscle length is important. Setting: Women’s Health Professional Hostel, Annamalai University. Study Design: Double blind analytical study Study Population: 50 subjects with age groups ranging from 18 to 25 years volunteered to participate in this study. Selection Criteria: Screening of all subjects to ensure that the tripod sign is positive. The participants will be selected with a normal body mass index (18.5 to 24.9 kg/m²) and be subjects who have no history of orthopedic or neurological disorders. Materials: Plinth Cloth straps Goniometer Tape measure Weighing Machine. Method: Four tests were assigned randomly to the four independent physiotherapists who were doing B.P.T. internships. The right lower extremity will be selected to perform the test. The four tests are: Straight Leg Raise (Stabilization Strap) test Straight Leg Raise (Low Back Flat) test Active Knee Extension test Passive Knee Extension test. Data were collected from four physiotherapists and statistically analyzed. Result: From the collected data, it shows that significant differences exist between SLR-SS, SLR-LBF mean difference (3.5), and P<0.05. Similarly, in AKE, the PKE mean difference is 6.7, and p<0.05. All four are highly correlated (r > 0.5). Conclusion: Hence, it was concluded that a significant relationship exists between all four tests. Both AKE and PKE are useful alternatives to SLR-SS and SLR-LBF.